Application of the HART protocol for communication with smart field devices - Mulaosmanović, Adnan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Smart instrumentation protocols are designed for applications where data is collected from instruments, sensors and actuators by digital communication technology. The HART protocol is a typical smart instrumentation Fieldbus. More than 40 million HART devices are installed worlwide, and the HART technology is the most widely usef field communication protocol for intelligent process instrumentation. Two communication channels supported by HART devices are the current loop 4-20 mA, and the HART digital channel. A digital communication channel simultaneously transmits information along the same wire and without disruption to the analog channel. This bi-directional communication channel provides a real time access to available data on HART smart devices. This paper deals with the properties and the application of the HART protocol. Introduction The HART protocol is a typical smart instrumentation Fieldbus that can operate in a hybrid 4–20 mA digital fashion. The HART communication protocol is an open standard owned by the HCF member companies. Products that use the HART protocol to provide both analog 4-20 mA and digital signals provide flexibility which is not available by any other communication technology. HART protocol properties (Basic Concept of HART) The HART communication protocol is based on the Bell 202 telephone communication standard and operates using the frequency shift keying (FSK) principle.This allows the superposition of the digital signal to an analog current signal. A digital signal is composed of two frequencies,1200Hz which represents the digital 1, and 2200Hz which represents the digital 0. Because the average value of the FSK signal is always zero, the 4–20 mA analog signal is not affected. HART protocol structure The HART protocol is implemented with the OSI model which is developed by the ISO (DIN ISO 7498). The OSI model provides the structure and all the necessary elements of the communication system. The HART protocol uses a reduced OSI model, where there are implemented only hree layers out of seven: a physical layer,  a data link layer, and an application layer. To make the intraction between HART devices as efficient as possible, classes of conformity have been established for masters as well as classes of commands for slaves. HART topologies HART devices can operate in one of two network configurations: either the point-to-point one or the multidrop one. The point-to-point topology is the most common way of connecting a HART device to the control system. In the point-to-point mode, the traditional 4–20 mA signal is used to communicate one process variable, while additional process variables, configuration parameters, and other device data are transferred digitally using the HART protocol. The multidrop mode is the main functionality of the HART protocol wanted by protocol designers. However,t due to its slow speed, it is rarely used in industry. More HART instruments can be connected to each other in parallel to a single pair of wires to exchange information between these instruments and the host. The multidrop mode requires only a single pair of wires and an auxiliary power supply unit which supplies up to15 devices (HART 5) or 62 devices (HART 7). In this mode, all field device polling addresses must be unique in a range of 1-15 (or 1-63), and the current through each device is fixed to a minimum value. Cables and power suply A theoretical limit for the cable length in the HART communication is 3000 meters. However, the electrical characteristics of the cable, mostly capacitance, as well as the combination of connected devices, can affect the maximum allowable cable length of the HART network. HART commands The HART commands are divided into three classes: Universal, Common Practice and Device Specific. All devices using the HART protocol must recognize and support the universal commands. The Common Practice commands provide functions that can be carried out by many but not all field devices. The Device Specific commands provide functions that are unique and restricted to an individual device. Wireless HART In addition to wired communication, the HART 7 includes wireless communication. The role of Wireless HART is to preserve the existing equipment and all the acquired knowledge in installation and maintenance, and also, by the use of wireless technologies, to reduce the price of installation of new measurement points, simplify access to advanced diagnostic information, and ensure better control over the equipment. The WirelessHART standard relies on the existing HART standard, the IEEE-802.15.4 standard, the AES-128 encryption and the DDL / EDDL technology. Conclusion It can be said that the HART protocol is one of the most popular ways to communicate with measuring equipment in industry. More modern digital standards in communication with field equipment, such as PROFIBUS and FOUNDATION Fieldbus providing similar or better performances as well as the HART protocol, are becoming increasingly popular in the industrial environment. However, it seems that the HART protocol will remain widely applied for many years. This is supported by the fact that the HART protocol continually evolves, and, as proof of this, there is the introduction of  revision 7 which defines wireless data transmission.
Keywords: HART protocol; signals; protocols; digitization